Crushed Aid: Fragmentation in Sectoral Aid - Emmanuel Frot; Javier Santiso (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
This paper measures and compares fragmentation in aid sectors. Past studies focused on aggregate country data but a sector analysis provides a better picture of fragmentation. We start by counting the number of aid projects in the developing world and find that, in 2007, more than 90 000 projects were running simultaneously. Project proliferation is on a steep upward trend and will certainly be reinforced by the emergence of new donors. Developing countries with the largest numbers of aid projects have more than 2 000 in a single year. In parallel to this boom of aid projects, there has been a major shift towards social sectors and, as a consequence, these are the most fragmented. We quantify fragmentation in each aid sector for donors and recipients and identify which exhibit the highest fragmentation. While fragmentation is usually seen as an issue when it is excessive, we also show that some countries suffer from too little fragmentation. An original contribution of this paper is to develop a monopoly index that identifies countries where a donor enjoys monopoly power. Finally, we characterise countries with high fragmentation levels. Countries that are poor, democratic and have a large population get more fragmented aid. However, this is only because poor and democratic countries attract more donors. Once we control for the number of donors in a country-sector, democratic countries do not appear different from non-democratic ones in any sector and poor countries actually have a slightly less fragmented aid allocation.
Keywords: F35; 330; Aid; Fragmentation